NEURO SCIENCE: CURRENT UNDERSTANDING AND IMPLICATION OF NEURO SCIENCE IN NEURO MARKETING - Dr. Poyam Sharma, Lt.(Dr.) Seema Singh, Ms. Shruti Srivastava (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Neuro Science has made add on advantages in the field of Neuro Science in the form of Neuro Marketing The Meaningful ways and the interaction of Neuro Science and Marketing Science has helped in generating the sense of understanding the behaviour of consumer. This blend of neuro science and marketing science led to the introduction of a new field of study which is nomenclature as NEURO MARKETING or CUNSUMER NEURO SCIENCE. Consumer Neuro Science is a new field of marketing which uses Functional Resonance Imaging through Medical Technologies to study brain responses to marketing stimuli FMRI is used to measure chances in the activity of a particular part of the brain and to study and learn why the consumer has taken the decision on the particular issue and subject and what part of brain is involved to make the decision they do and which part is responsible to do so